Cytotoxic and Antiviral Activities of Colombian Medicinal Plant Extracts of the Euphorbia genus (2002)
ABSTRACT: Forty-seven plant extracts of 10 species of the genus Euphorbia (Euphorbiaceae) used by Colombian traditional healers for the treatment of ulcers, cancers, tumors, warts, and other diseases, were tested in vitro for their potential antitumour (antiproliferative and cytotoxic) and antiherpetic activity. To evaluate the capacity of the extracts to inhibit the lytic activity of herpes simplex virus type 2 (HSV-2) and the reduction of viability of infected or uninfected cell cultures, the end-point titration technique (EPTT) and the MTT [3-(4,5-dimethylthiazol–2-yl)- 2,5-diphenyltetrazolium bromide] colorimetric assay were used, respectively. The therapeutic index of the positive extracts for the antiviral activity was determined by calculating the ratio CC50 (50% cytotoxic concentration) over IC50 (50% inhibitory concentration of the viral effect). Five of the 47 extracts (11%) representing 3 out of 10 Euphorbia species (30%) exhibited antiherpetic action; the highest activity was found in the leaf/stem watermethanol extracts from E. cotinifolia and E. tirucalli. The therapeutic indexes of these two plant species were > 7.1; these extracts exhibited no cytotoxicity. Six extracts (13%) representing 4 plant species (40%) showed cytotoxic activity. The highest cytotoxicity was found in the dichloromethane extract obtained from E. cotinifolia leaves and the CC50 values for the most susceptible cell lines, HEp-2 and CHO, were 35.1 and 18.1 µg/ml, respectively.